O pauperismo como equilíbrio econômico : as hagiografias e as engrenagens da materialidade na ordo fratrum minorum (1228-1263) - Martins, Douglas de Freitas Almeida (2015)
In this dissertation, we analyze the Minorite hagiographies written along the thirteenth century as as documents that carried an economic ethos. Filled with idealized values by the Order of Friars Minor, these narratives have become a model for the recognition and legitimation of the functions that the Order could take towards the society in material expansion of the medieval Italian cities. To perform such an analysis was necessary to use concepts that escape the natural and manichaean approaches that highlight material life as a social field apart from other historical experiences. The hagiographic texts were interpreted with the support of theoretical formulations of Economic Primitivism, highlighting the names of Karl Polanyi and Max Weber. From the use of the method known as "evidential paradigm", Carlo Ginzburg proposed, treat the signs and the small details as evidence that reveal a greater reality - an ethos devised regarding the insertion of the friars in the urban materiality of the thirteenth century principles. The hypothesis guiding this investigation is that: the hagiographies were vehicles for the transmission of a particular status , which, having Francis of Assisi character as a central element, articulated the ideals of pauperism, charity and brotherhood as a means for the insertion of the friars in the areas called economic - and not the denial of it. In these pages we discuss the values associated with redistribution of surplus, the legitimation of forms of status and the model of the Order as a paterfamilias and dispenser of material life.